Perbedaan Hasil dan Kualitas Ubi Jalar (Ipomoea Batatas L.) Akibat Perendaman Stek Menggunakan Ekstrak Bawang Merah - Lia Aulia; Hanny Hidayati Nafi'ah; Hendrawan Hendrawan (Ma'soem University, 2022)
One of the obstacles to the cultivation of sweet potatoes planted in the dry season is the lack of seedlings. One solution is to use cuttings that are cut smaller than the size of the cuttings should be. To increase the growth and yield of sweet potatoes, shallot extract is used as an exogenous hormone as a pre-planting treatment. The purpose of this study was to determine the effect of onion extract and soaking duration on the yield and quality of sweet potato. This experiment was carried out from March to June 2021 in the experimental field of the Faculty of Agriculture, University of Garut, Tarogong Kaler District, Garut Regency with an altitude of 761 meters above sea level. This experiment used a non-factorial randomized block design with nine treatments repeated three times. The concentration of shallot extract and the duration of soaking affect the weight of tuber per plant, the weight of tuber per plot, the weight of economical tuber per plot, the weight of non-economical tuber per plot and the brix test of fresh tuber. The best results were found in the treatment of shallot extract concentration of 90% and soaking duration of 90 minutes.